Legitimacy as Resource: How Did the Presidential Impeachment in South Korea Succeed? - Kim, Phil(김필); Im, Tobin(임도빈) (한국조직학회보, 2022)
This study retrospectively examines how the South Korean government tackled the “2016 Candlelight Protest” which ended with the impeachment of the then-President Park Geun-hye. To understand the rally’s impact on impeachment decision, we trace strategies of the Blue House and a civil organization named “Park Geun-hye Resignation Nationwide Movement.” Resource dependence theory has been adopted to explain the shift from one stage to another, in a sequence of four critical turning points of the process: 1) the outset of the scandal, 2) the third candlelight protest rally, 3) impeachment vote, and 4) the verdict of the Constitutional Court. The key finding is that when two conflicting forces collide multiple times in different stages, their chosen strategies in accumulation determine the end resulting equilibrium point. “Compliance” and “management” strategies, which are more extreme ways for an organization to cope with the state of affairs, work more effectively than “avoidance” strategy. KCI Citation Count: 0